Two new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from Thailand - Sukprasert, Apisak; Sutthiwises, Surapop; Lauhachinda, Virayuth; Taksintum, Wut (Zootaxa, 2018)
We investigate the taxonomy of slender geckos (Hemiphyllodactylus) in Thailand by means of molecular phylogenetics and morphological study using specimens from three provinces; Chiang Mai, Kamphaeng Phet, and Chanthaburi. The results of phylogenetic analyses had shown that the genetic data of populations from 2 provinces were distinctly different from known species. In addition, some morphological characters of these two populations such as lamellar formula on fore- and hindfoot differed from the other species. The integrated taxonomy using molecular phylogenetics and morphological study revealed two new species, Hemiphyllodactylus khlonglanensis sp. nov. from western Thailand, and Hemiphyllodactylus flaviventris sp. nov. from eastern Thailand as described herein.